Mesenchymal stem cells enhanced with SeNPs protection against CLP induction associated with liver injury are mediated via antioxidant, anti-inflammatory, and immunomodulatory activities - Abd El Aleem, Asmaa M. M.; El-Khadragy, Manal F.; Abdel Moneim, Ahmed E.; Agwa, Sara H.; Abou Zahra, Fatma; Abdalla, Mohga S. (Frontiers in Immunology, 2025)
IntroductionSepsis-induced liver injury is a serious issue in critical care. Since antibiotics are insufficiently effective to combat the disease and avoid upcoming organ failure, treatment with mesenchymal stem cells (MSCs) is an alternate strategy for treating liver damage. Thus, our work aimed to boost the therapeutic potential of MSCs by pretreating them with selenium in the form of sodium selenite (Na₂SeO₃) and selenium nanoparticles (SeNPs) in the cecal ligation and puncture (CLP) rat model of sepsis.MethodsRats were split into groups that received MSCs alone, MSCs enhanced with Na₂SeO₃ (E1-MSCs), MSCs enhanced with SeNPs (E2-MSCs), antibiotics (Ab), and no therapy (CLP), in addition to the control and sham groups. Within 48 hours of the operation, liver tissues and blood samples were taken.ResultsMSC treatment, significantly augmented with selenium compounds, markedly reduced markers of liver injury and signs of oxidative stress (MDA, MPO, NO) while elevating levels of GSH and antioxidant enzymes (GPx, GR, SOD, CAT). Furthermore, the therapies attenuated pro-inflammatory cytokines (TNF-α, IL-1β, IL-8) and inflammatory pathways (iNOS, MAPK9, NF-κB). Additionally, MSCs and enhanced MSCs improved hepatic tissue by alleviating the immunomodulatory indicators (COX-2, PGE2) and regulating apoptosis by raising (Bcl-2) and minimizing (Cas-3 and Bax). Histopathological analysis showed that MSC therapies, particularly when enhanced, restored the natural architecture of the liver.DiscussionThis study concludes that MSCs enhanced with selenium compounds provide a promising therapeutic approach for liver dysfunction caused by sepsis, possibly through regulating antioxidants, anti-inflammatory processes, immunology, and hepatic tissue regeneration.